2010
DOI: 10.2215/cjn.01270210
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Gentamicin-Resistant Bacteremia in Hemodialysis Patients Receiving Gentamicin Lock Catheter Prophylaxis

Abstract: Results: Within the first year of the GHL protocol, our CRI rate decreased from 17 to 0.83 events per 1000 catheter-days. Beginning 6 months after initiation of the GHL protocol, febrile episodes occurred in 13 patients with coagulase-negative Staphylococcus bacteremia resistant to gentamicin. Over the 4 years of GHL use, an additional 10 patients developed 11 episodes of gentamicin-resistant CRI (including 7 with Enterococcus faecalis), in which there were 4 deaths, 2 cases of septic shock requiring intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 30 publications
0
107
2
3
Order By: Relevance
“…Concerns remain over the risk of bacterial resistance developing when antibiotic solutions are used and the potential side effects of some antibiotics 35 . One randomized controlled study in 110 HD patients showed that taurolidine (1.35%)/citrate lock (4%) solution did not reduce bacteremia rates from any cause with t-HDC 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Concerns remain over the risk of bacterial resistance developing when antibiotic solutions are used and the potential side effects of some antibiotics 35 . One randomized controlled study in 110 HD patients showed that taurolidine (1.35%)/citrate lock (4%) solution did not reduce bacteremia rates from any cause with t-HDC 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Our observational study of .1400 patients followed for .4 years used heparin with a high-dose gentamicin locking solution (4 mg/ml) but did not have comparison resistance data from a historical control period (21). We used povidone-iodine rather than chlorhexidine as the skin antiseptic and covered the exit site with mupirocin, which has been associated with bacterial resistance (22).…”
mentioning
confidence: 99%
“…In the largest of those studies, gentamicin use resulted in a significant reduction in catheter-related bacteremia, but infections with gentamicin-resistant organisms emerged within 6 months (14). Although those studies involved intraluminal instillation of gentamicin and not topical application, the findings suggest that chronic prophylactic exposure to aminoglycosides can breed resistance.…”
Section: Discussionmentioning
confidence: 99%